Effectiveness Test of Soursop Leaf Ethanol Extract (Annona muricata L) as a Healer of Incision Wounds on Mice (Mus musculus) Skin - Novianti Cahyani Junadi; Sri Yolandari; Suparman Supardi (Journal of Health Science and Pharmacy, 2026)
Background: Annona muricata (soursop) is a traditional medicinal plant widely used for wound treatment. Incision wounds are tissue injuries caused by sharp objects and may vary in severity from mild to severe. The wound healing process involves inflammatory, proliferative, and maturation phases, which can be influenced by bioactive compounds derived from natural products. Objectives: This study aimed to determine the effectiveness of ethanol extract of soursop leaves (Annona muricata L.) in accelerating the healing of incision wounds in Mus musculus. Methods: The extract was prepared using a maceration method of dried soursop leaf simplicia with 96% ethanol. A total of 15 white mice (Mus musculus) were divided into five treatment groups: (1) negative control (distilled water), (2) positive control (10% povidone iodine), (3) extract dose of 0.1 g, (4) extract dose of 0.2 g, and (5) extract dose of 0.3 g. An incision wound was made on the dorsal area of each mouse. Treatments were administered once daily for 14 days. Data were analyzed using one-way ANOVA followed by the Post Hoc LSD test to determine significant differences between groups. Results: The findings indicated that the ethanol extract of soursop leaves accelerated incision wound healing in mice, with the 0.3 g dose showing the highest effectiveness. Statistical analysis using one-way ANOVA revealed a significant difference among treatment groups (p < 0.05; p = 0.000). Further analysis using the Post Hoc LSD test confirmed significant mean differences between groups. Conclusion: The ethanol extract of soursop leaves (Annona muricata L.) is effective in accelerating incision wound healing in Mus musculus, with the 0.3 g dose demonstrating the most optimal effect. Keywords: Annona muricata L.; incision wounds; Mus musculus; ethanol extract; wound healing